ANTIOXIDANT AND ANTIMICROBIAL ACTIVITIES OF LEAVES OF MEDICINAL PLANT Hibiscus tiliaceus L. - Nilsya Febrika Zebua; Nerdy Nerdy; Refi Bahrianur; Shadiq Suwailim; Said Haikal Alfajar (Universitas Haji Sumatera Utara, 2024)
Antimicrobial agents are very important in the medical world. The agent is used as a surgical and intensive care procedure. However, bacteria have become resistant to the antibiotics used. Apart from that, antioxidants are also needed in the medical world as neuroprotectives and preventing free radicals in the body so as to avoid degenerative diseases. Hibiscus tiliaceus L or better known in Indonesia is a waru plant, containing various active compounds such as alkaloids, flavonoids, tannins and saponins that can be used as alternatives as natural antimicrobials and antioxidants. The purpose of writing this review article is to determine the antimicrobial and antioxidant potential of hibiscus plants (Hibiscus tiliaceus L.). The method used in this review article is a literature study obtained from sciencedirect, researchgate and google scholar regarding the benefits of Hibiscus tiliaceus L. leaf extract as an antimicrobial and antioxidant through a literature search process using research articles from the last 10 years. Based on research that has been carried out, it shows that Hibiscus tiliaceus L. leaves extract has the potential to be a natural antimicrobial and antioxidant.